2016
DOI: 10.3892/ol.2016.4329
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 agonist induced repression of hepatocellular carcinoma via the TLR7-IKK-NF-κB-IL6 signaling pathway

Abstract: Toll-like receptors (TLRs) are key members of innate immunity, involved in the defense against diseases, and evidence has revealed that TLR4/5 is involved in the carcinogenesis of hepatic cancer. TLR7 belongs to the TLR family, and its roles in immune-associated hepatic diseases have been well characterized; however, the consequences of agonist targeting of TLR7 in hepatic cancer have not previously been reported. The present study aimed to investigate the effects and underlying mechanisms of Imiquimod, a TLR7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…The HH signaling pathway may also induce TGF-β signaling that further activates MAP3K7 (28). The IKK-NF-κB signaling pathway upregulates the expression of Snail2 (29). Ma et al reported that activated HH in CAF can promote the invasion and metastasis of tumor cells via paracrine action (30).…”
Section: Discussionmentioning
confidence: 99%
“…The HH signaling pathway may also induce TGF-β signaling that further activates MAP3K7 (28). The IKK-NF-κB signaling pathway upregulates the expression of Snail2 (29). Ma et al reported that activated HH in CAF can promote the invasion and metastasis of tumor cells via paracrine action (30).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other circular RNAs and microRNAs act as post-transcriptional modifiers of genes linked to the IKK/NF-κB signaling pathway in the liver [47]. Moreover, dysregulation of the IKK-NF-κB-IL-6 signaling pathway has been linked to the development of HCC [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…TLR7 is a member of the TLR family that acts as a pattern recognition receptor and is expressed on the membrane of endosomes. TLR7 activation by ssRNA of virals and nucleic acids can induce the expression of type I interferon and inflammatory cytokines, and activate other immune cells through several signaling pathways, such as the NF-κB signaling pathway [ 34 , 35 ]. Considering the powerful immune regulatory function of TLR7, the agonists of TLR7 have been approved for topical application in cancer treatment [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%